Role of post-replication and excision repair mechanism in the induction of Trp+ revertants of UV-irradiated Escherichia coli - Balgavý, P; Rauko, P (Folia microbiologica, 1976)
Both the post-replication and the excision repair mechanism participate in the induction of Trp+ revertants in Escherichia coli B/r Hcr+ thy trp after a UV-irradiation. At low radiation doses (surviving cell fraction greater than 10(-1) most Trp+ reversions are due to post-replication repair mechanism while at high doses (surviving cell fraction less than 10(-1)) the Trp+ reversions arise probably as the result of an inaccurate excision repair. The absolute accuracy of repair processes decreases with increasing radiation dose.
Keywords: Radiation Effects; DNA Repair; mutace; tryptofan; DNA bakterií; DNA, Bacterial; Ultraviolet Rays; Thymine; Escherichia coli; radiační účinky; vztah dávky záření a odpovědi; thymin; Mutation; Tryptophan; Dose-Response Relationship, Radiation; ultrafialové záření; oprava DNA